Composite current collector, method for manufacturing the same, and battery

CN123017858APending Publication Date: 2026-10-30JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611337293.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是,该转接焊工艺新增了焊接工序,在超声波焊接过程中,高分子材料的柔软特性会大量吸收超声波振动能量,极易出现虚焊、焊穿及高分子熔融残留等问题,严重影响电芯良率和生产效率

Benefits of technology

(1)本发明通过在高分子基材上预设的极耳区先涂布离型层,使得后续沉积的金属层在该区域与基材之间形成极低附着力的界面。随后通过物理剥离将极耳区的金属层“掀开”,再切除暴露出的基材和离型膜,最终在极耳区形成仅由金属层构成的“纯金属结构”。该纯金属焊接区可直接与极耳进行焊接,形成牢固的冶金结合,彻底避开了高分子基材对焊接质量的干扰;同时纯金属层与极耳之间形成直接的金属-金属冶金结合,接触电阻极低,有效降低了电池内阻,提升了倍率充放电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of composite current collector and its preparation method and battery, it is related to current collector technical field.The application is by in the tab area of polymer matrix coating release coating and solidification forms release layer;The polymer matrix coated with the release layer is carried out metallization deposition treatment, and forms metal conductive layer on the surface of polymer matrix;The metal conductive layer of tab area is stripped from the surface of release layer, and the release layer and polymer matrix of tab area are exposed;Exposed release layer and polymer matrix are removed, and make tab area form pure metal welding area, and prepare composite current collector.The method is by " release + stripping + cutting " process, and forms the pure metal structure without polymer matrix in tab area, can be directly welded with tab, without adapter welding, solves the problem that conventional composite current collector cannot be directly welded due to intermediate insulating layer.The composite current collector prepared by the application has high welding strength, low contact resistance, and the process is environmentally friendly and suitable for continuous production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery current collector technology, and more specifically, to a composite current collector, its preparation method, and a battery. Background Technology

[0002] Composite current collectors are functional thin films composed of multiple layers of materials, typically employing a "metal-polymer-metal" sandwich structure. An insulating polymer material forms the middle layer, with conductive metal layers such as copper or aluminum plated on both sides. They are primarily used to replace traditional pure metal foil as the positive and negative electrode current collectors in batteries. For traditional pure metal foil current collectors, the tabs are usually formed by leaving uncoated areas during the coating of the active material. After die-cutting, the multiple layers of electrodes in these uncoated areas are directly welded together to achieve electrical conductivity between the layers. A nickel sheet is then welded to connect to the external electrode lead. However, because the middle layer of a composite current collector is an insulating polymer material, directly die-cutting and welding the multiple layers results in extremely poor mechanical strength at the weld points, making them prone to separation.

[0003] To address this issue, existing technologies typically employ an adapter welding process. This involves ultrasonically welding an adapter layer onto at least one side of the blank area of ​​the composite current collector, followed by die-cutting. The die-cut composite current collector is then welded integrally with the adapter layer to form a high-strength welded structure, and finally, the nickel sheet and electrode leads are welded on. However, this adapter welding process adds a welding step. During ultrasonic welding, the flexible nature of the polymer material absorbs a large amount of ultrasonic vibration energy, easily leading to problems such as incomplete welds, burn-through, and residual polymer melt, severely impacting cell yield and production efficiency. Therefore, providing a composite current collector that can achieve reliable welding without adapter welding and its preparation method has become a pressing technical problem in this field. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a composite current collector, its preparation method, and a battery. By forming a pure metal tab region through "release + peeling + cutting", the composite current collector can achieve reliable welding without the need for transfer welding.

[0005] This invention is implemented as follows: In a first aspect, the present invention provides a method for preparing a composite current collector, comprising the following steps: A release coating is applied to the tab area of ​​a polymer substrate, and a release layer is formed after curing. Metallization deposition is performed on the polymer substrate coated with the release layer to form a metal conductive layer on the surface of the polymer substrate. The metal conductive layer of the tab region is peeled off from the surface of the release layer to expose the release layer and the polymer substrate of the tab region; Remove the exposed release layer and the polymer substrate to form a pure metal welding area in the tab region, thus obtaining a composite current collector; The tab region of the polymer substrate is the area on the polymer substrate that is connected to the tab through the metal layer after the metal conductive layer is deposited.

[0006] In an optional embodiment, the polymer substrate is selected from polyethylene terephthalate, polypropylene, or polyimide, and has a thickness of 2μm-10μm. And / or, the polymer substrate further includes dust removal treatment and corona treatment before coating, wherein the power of the corona treatment is 2kW-5kW and the treatment speed is 20m / min-50m / min; And / or, the release layer comprises a release host, a reactive monomer, and a photoinitiator in a mass ratio of (50-80):(10-30):(0.5-2); And / or, the thickness of the release layer is 0.01 μm-0.1 μm; And / or, the thickness of the metal conductive layer is 0.5μm-2μm.

[0007] In an optional embodiment, the preparation of the release coating includes: mixing the release substrate, reactive monomer and photoinitiator in a mass ratio of (50-80):(10-30):(0.5-2), adding solvent and mixing evenly to obtain the release coating; Preferably, the solvent is selected from at least one of ethyl acetate and butyl acetate; And / or, the solid content of the release coating is 10%-40%; And / or, the release body comprises hexenyl polydimethylsiloxane; And / or, the reactant monomer is at least one of hexafluorobutyl acrylate and perfluoroalkyl ethyl acrylate; And / or, the photoinitiator is at least one selected from 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and ethyl 2,4,6-trimethylbenzoylphosphonate.

[0008] In an optional embodiment, the coating method is micro-grooved roller coating, slot coating or spraying, with a coating speed of 60mm / s-80mm / s and a coating width of 1mm-8mm. And / or, the curing method is ultraviolet light curing, with an ultraviolet light intensity of 600 mJ / cm. 2 -1000mJ / cm 2 The curing time is 2-5 seconds. And / or, the peel force of the metal conductive layer and the release layer is ≤10N / m.

[0009] In an optional embodiment, the preparation of the metal conductive layer includes depositing the metal conductive layer on the surface of a polymer substrate by a deposition process; Preferably, the deposition process includes at least one of magnetron sputtering, vacuum evaporation, and electroplating. Preferably, the metal layer is prepared by vacuum evaporation to form a metal layer with a thickness of 0.5 μm-2 μm on the surface of a polymer base film; Preferably, the preparation of the metal layer includes first forming a metal seed layer with a thickness of 30nm-50nm on the surface of a polymer base film by magnetron sputtering, and then thickening the metal layer to 0.5μm-2μm by electroplating.

[0010] In an optional embodiment, when peeling the metal conductive layer of the tab region from the release layer surface, adhesive tape peeling or vacuum adsorption peeling is used. Preferably, the tape is a high-adhesion polyimide tape or an acrylic tape; Preferably, the peeling angle during peeling is 90°-180°, and the peeling speed is 1m / min-20m / min; And / or, the release layer and polymer substrate of the tab area are removed by laser cutting or hot knife cutting; Preferably, the laser cutting parameters are: a nanosecond laser or a picosecond laser is used, the laser wavelength is 243nm-455nm, the laser power is 15W-50W, the pulse frequency is 200kHz-1000kHz, and the cutting speed is 200mm / s-300mm / s. Preferably, the parameters for hot knife cutting are: cutting temperature of 200℃-400℃, cutting pressure of 0.1MPa-1.0MPa, and cutting speed of 10mm / s-100mm / s.

[0011] In an optional embodiment, after removing the release layer and polymer substrate of the tab region, the step of cleaning the metal surface of the tab region is further included to remove surface oxides and release layer residues. Preferably, the cleaning is performed by wiping the surface of the welding area with a lint-free cloth soaked in an organic solvent, wherein the organic solvent is anhydrous ethanol or acetone.

[0012] Secondly, the present invention provides a composite current collector, which is prepared by any of the preparation methods described in the foregoing embodiments.

[0013] Thirdly, the present invention provides an electrode sheet that employs the composite current collector as described in the foregoing embodiments.

[0014] Fourthly, the present invention provides a battery employing the electrode plates described in the foregoing embodiments.

[0015] The present invention has the following beneficial effects: (1) In this invention, a release layer is first coated on a pre-defined tab area on a polymer substrate, so that the subsequently deposited metal layer forms an interface with extremely low adhesion between the tab area and the substrate. Then, the metal layer in the tab area is "lifted" by physical peeling, and the exposed substrate and release film are removed, ultimately forming a "pure metal structure" consisting only of a metal layer in the tab area. This pure metal welding area can be directly welded to the tab to form a strong metallurgical bond, completely avoiding the interference of the polymer substrate on the welding quality; at the same time, a direct metal-metal metallurgical bond is formed between the pure metal layer and the tab, with extremely low contact resistance, effectively reducing the internal resistance of the battery and improving the rate charge and discharge performance.

[0016] (2) This solution adopts the "release + physical peeling" method, which does not require the use of a large amount of strong acid and strong alkali etching solution, has no wastewater and exhaust gas emissions, has low environmental pressure, high material utilization rate, and lower overall manufacturing cost; and the processes such as local coating, peeling and cutting of substrate can be continuously produced by winding and unwinding equipment, with strong process compatibility and easy to mass-produce on a large scale. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0018] The following is a detailed description of the composite current collector, its preparation method, and the battery proposed in this invention.

[0019] A first aspect of the present invention provides a method for preparing a composite current collector, comprising the following steps: S1. A release coating is applied to the tab area of ​​the polymer substrate, and a release layer is formed after curing; the tab area of ​​the polymer substrate is the area used to connect with the tab through the metal layer after the metal conductive layer is deposited on the polymer substrate.

[0020] The polymer substrate is selected from polyethylene terephthalate (PET), polypropylene (PP) or polyimide (PI), and has a thickness of 2μm-10μm, for example, it can be 2μm, 6μm, 8μm or 10μm.

[0021] In some preferred embodiments, the polymer substrate roll is mounted on an unwinding device. Before coating, the polymer substrate needs to undergo dust removal and corona treatment. Preferably, dust removal is performed using a dust removal roller or an ion gun to remove surface particulate impurities. The power of the corona treatment is 2kW-5kW, for example, 2kW, 3kW, 4kW, or 5kW. The treatment speed is 20m / min-50m / min, for example, 20m / min, 30m / min, 40m / min, or 50m / min, to improve the surface tension of the substrate and ensure the uniformity of the release agent coating.

[0022] In the embodiments of this application, the preparation of the release coating includes: mixing the release substrate, reactive monomer and photoinitiator in a mass ratio of (50-80):(10-30):(0.5-2), adding solvent and mixing evenly to obtain the release coating; As an example, the mass ratio of the release substrate, reactive monomer, and photoinitiator can be 50:10:0.5, 60:20:1, 70:30:1.5, or 80:30:2, etc.

[0023] The solid content of the release coating is 10%-40%, for example, it can be 10%, 20%, 30% or 40%; Preferably, the release agent is hexenyl polydimethylsiloxane; the reaction monomer is hexafluorobutyl acrylate or perfluoroalkyl ethyl acrylate; the photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and ethyl 2,4,6-trimethylbenzoylphosphonate; and the solvent is at least one of ethyl acetate and butyl acetate.

[0024] In some embodiments of this application, the coating method is micro-grooved roller coating, slot coating or spraying, and the coating speed is 60 mm / s-80 mm / s, for example, 60 mm / s, 70 mm / s or 80 mm / s; the coating width is 1-8 mm, for example, 1 mm, 2 mm, 4 mm, 6 mm or 8 mm. The curing method is ultraviolet light curing, with an ultraviolet light intensity of 600 mJ / cm. 2 -1000mJ / cm 2 For example, it can be 600 mJ / cm 2 700 mJ / cm 2 800 mJ / cm 2 900 mJ / cm 2 Or 1000 mJ / cm 2 The curing time is 2s-5s, for example, it can be 2s, 3s, 4s or 5s, etc.

[0025] Furthermore, the thickness of the release layer after curing is 0.01μm-0.1μm, for example, it can be 0.01μm, 0.02μm, 0.04μm, 0.06μm, 0.08μm or 0.1μm, etc.

[0026] S2. Perform metallization deposition treatment on the polymer substrate coated with the release layer to form a metal conductive layer on the surface of the polymer substrate. Specifically, the preparation of the metal conductive layer includes depositing the metal conductive layer on the surface of a polymer substrate through a deposition process; further, the deposition process includes at least one of magnetron sputtering, vacuum evaporation, and electroplating. Even further, the preparation of the metal layer includes forming a metal layer with a thickness of 0.5 μm-2 μm on the surface of the polymer base film through vacuum evaporation; Alternatively, the metal layer can be prepared by first forming a metal seed layer with a thickness of 30 nm-50 nm on the surface of a polymer substrate film by magnetron sputtering, and then thickening the metal layer to 0.5 μm-2 μm by electroplating. S3. The metal conductive layer of the tab region is peeled off from the surface of the release layer to expose the release layer and the polymer substrate of the tab region; Specifically, the composite current collector roll material obtained in step S2 is installed on the unwinding equipment, the web correction system is activated, and visual / photoelectric positioning is performed in conjunction with the positioning marks (such as color marks or cursors printed on the edge of the release layer) set on the composite current collector to accurately identify and mark the position of the welding area in the width and length directions of the roll material.

[0027] In this application, the release layer, after curing, has extremely low surface energy. When the metal conductive layer is deposited on the surface of the release layer, only weak van der Waals forces are formed between the metal atoms or clusters and the surface of the release layer, and chemical bonding or a strong mechanical interlocking structure cannot be formed. Therefore, the peel force between the metal conductive layer and the release layer can be controlled below 10 N / m. This peel force is significantly lower than the fracture strength of the metal conductive layer itself, and also lower than the adhesion force of the tape to the metal layer or the adsorption force of the vacuum adsorption device, thereby ensuring that the metal conductive layer maintains its intact shape during the peeling process, and only interlayer separation occurs without fracture or plastic deformation.

[0028] Therefore, after determining the location of the welding area, the edge of the metal layer at the welding area is fixed by physical means, such as by tape or vacuum adsorption. (1) Applying release tape: Apply release tape to the surface of the metal layer in the welding area. The adhesive force of the selected release tape to the metal layer must be greater than the peel force between the metal layer and the release layer. Preferably, the release tape is a high-adhesion polyimide tape or an acrylic tape.

[0029] (2) Vacuum adsorption fixation: The edge of the metal layer in the welding area is adsorbed and fixed by a vacuum adsorption device.

[0030] When it is necessary to peel off the metal layers on both sides of the composite current collector at the same time, the above operation can be carried out simultaneously on the upper and lower surfaces of the composite current collector, that is, by attaching peeling tape or setting up vacuum adsorption devices separately.

[0031] After fixation, apply an external force away from the release layer to the release tape, or activate the traction mechanism of the vacuum adsorption device to peel the metal layer of the welding area off the surface of the release layer. During the peeling process, the magnitude and direction of the external force must be controlled to keep the metal layer intact (i.e., only interlayer separation occurs without ductile fracture), and the metal layer is in a "lifted" or "uncovered" state, thus fully exposing the release layer and substrate surface underneath.

[0032] To ensure the integrity and efficiency of the metal layer during the peeling process, the peeling angle is 90°-180°, and the direction of the peeling force is at a large angle to the normal direction of the release layer surface. The peeling stress is concentrated at the metal layer / release layer interface, rather than being transmitted to the interior of the metal layer, thus avoiding plastic deformation or fracture of the metal layer. The peeling speed is 1m / min-20m / min, ensuring that the peeling process is in a quasi-static or low-speed dynamic range, avoiding stress concentration and brittle fracture caused by high-speed peeling.

[0033] S4. Remove the exposed release layer and the polymer substrate to form a pure metal welding area in the tab region, thereby obtaining a composite current collector.

[0034] In some preferred embodiments, the exposed release layer and the insulating polymer substrate corresponding to the tab area are removed by laser cutting or hot knife cutting. The laser cutting parameters are as follows: a nanosecond laser or a picosecond laser is used; the laser wavelength is 243nm-455nm, for example, 243 nm, 250 nm, 300 nm, 350 nm, 400 nm, or 450 nm; the laser power is 15W-50W, for example, 15 W, 20 W, 25 W, 30 W, 35 W, 40 W, 45 W, or 50 W; the pulse frequency is 200kHz-1000kHz, for example, 200 kHz, 300 kHz, 400 kHz, 500 kHz, 600 kHz, 700 kHz, 800 kHz, 900 kHz, or 1000 kHz; and the cutting speed is 200mm / s-300mm / s, for example, 200 mm / s, 250 mm / s, or 300mm / s. The parameters for hot knife cutting are as follows: cutting temperature is 200℃-400℃, for example, 200℃, 250℃, 300℃, 350℃ or 400℃; cutting pressure is 0.1MPa-1.0MPa, for example, 0.1MPa, 0.2MPa, 0.4MPa, 0.6MPa, 0.8MPa or 1.0MPa; cutting speed is 10mm / s-100mm / s, for example, 10 mm / s, 20 mm / s, 30 mm / s, 40 mm / s, 50 mm / s, 60 mm / s, 70 mm / s, 80 mm / s, 90 mm / s or 100 mm / s.

[0035] In addition, after removing the exposed release layer and the insulating polymer substrate corresponding to the tab area, the surface of the pure metal welding area is wiped with a lint-free cloth soaked in organic solvent to remove surface oxides and release agent residue; the organic solvent is anhydrous ethanol or acetone.

[0036] A second aspect of the present invention provides a composite current collector, which is prepared by the preparation method described in any one of the foregoing embodiments.

[0037] A third aspect of the present invention provides an electrode sheet employing the composite current collector as described in the foregoing embodiments.

[0038] A fourth aspect of the present invention provides a battery employing electrode plates as described in the foregoing embodiments.

[0039] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0040] Example 1 This embodiment provides a method for preparing a composite current collector, including the following steps: (1) The polymer substrate is PET film with a thickness of 6μm. The PET roll is installed on the unwinding equipment and then passes through the dust removal roller and corona treatment in sequence. The corona treatment power is 3kW and the processing speed is 30m / min; (2) Preparation of release coating: Hexenyl polydimethylsiloxane (release substrate), hexafluorobutyl acrylate (reactant monomer), and 2-hydroxy-2-methyl-1-phenylpropanone (photoinitiator) were mixed at a mass ratio of 70:20:1. Ethyl acetate solvent was added and mixed evenly to prepare a release coating with a solid content of 25%. The release coating was applied to the tab area of ​​the PET film surface using a micro-grooved roller coating method. The coating speed was 70 mm / s, and the coating width was 5 mm. After coating, it was immediately cured by ultraviolet irradiation with an intensity of 800 mJ / cm. 2The curing time is 3 seconds, the thickness of the release layer after curing is 0.05 μm, and the peel force between the release layer and the copper layer after curing is approximately 4 N / m; the PET film has release layers on both surfaces. (3) Double-sided copper plating is performed on the PET film coated with the release layer. The PET film coated with the release layer is placed in the vacuum chamber of the magnetron sputtering equipment, and the vacuum is evacuated to a vacuum degree of 5×10⁻⁶. -4 Argon gas was introduced to maintain the chamber pressure at 0.5 Pa. A copper seed layer was deposited on the substrate surface using a sputtering power of 10 kW, a substrate travel speed of 5 m / min, and a copper seed layer thickness of 50 nm. The substrate with the copper seed layer was then transferred to an electroplating line, where an acidic copper plating solution was used for electroplating. The solution pH was 3, the current density was 8 ASD, the plating temperature was 30 °C, and the total copper layer thickness on one side was 1.5 μm. (4) Install the roll material prepared in step (3) onto the unwinding equipment, start the correction system, and use the CCD vision system to identify the printed positioning marks on the edge of the release layer to accurately mark the tab area. Adhere high-adhesion polyimide tape to the copper layer surface in the tab area, ensuring that the tape is fully adhered to the copper layer. Then, at a peeling angle of 135° and a peeling speed of 10m / min, peel the copper layers on the upper and lower surfaces completely from the release layer surface until the release layer surface is fully exposed. The copper layer maintains a complete sheet shape during the peeling process, without breakage or wrinkles.

[0041] (5) A nanosecond laser is used to cut and remove the exposed release layer and the corresponding PET substrate in that area. The laser wavelength is 355nm, the laser power is 30W, the pulse frequency is 500kHz, and the cutting speed is 250mm / s. After cutting, only the copper metal layer remains in the tab area, forming a pure copper welding area. Then, a lint-free cloth soaked in anhydrous ethanol is used to wipe the inner and outer surfaces of the copper metal layer in the tab area to remove residual oxides and release agent residues, thus obtaining the composite current collector.

[0042] Example 2 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as in Embodiment 1, the only difference being: (1) The polymer substrate is PP film with a thickness of 4μm. The corona treatment power is 4kW and the treatment speed is 40m / min; (2) In the release coating, the mass ratio of the release substrate, reactive monomer (perfluoroalkyl ethyl acrylate), and photoinitiator (1-hydroxycyclohexylphenyl ketone) is 60:25:1.5, the solvent is butyl acetate, and the solid content is 30%. The coating speed is 60 mm / s, the coating width is 2 mm, and the release layer thickness is 0.03 μm; (3) The copper seed layer thickness is 40 nm, the sputtering power is 12 kW, and the substrate travel speed is 8 m / min. The electroplating current density is 5 ASD, the electroplating temperature is 35℃, and the total thickness of the copper layer on one side is 1.0 μm.

[0043] Example 3 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as in Embodiment 1, the only difference being: (1) The polymer substrate is a PI film with a thickness of 8 μm. The corona treatment power is 2.5 kW and the treatment speed is 25 m / min; (2) In the release coating, the mass ratio of the release substrate, the reactive monomer (hexafluorobutyl acrylate), and the photoinitiator (ethyl 2,4,6-trimethylbenzoylphosphonate) is 75:15:0.8, the solvent is a mixture of ethyl acetate and butyl acetate (volume ratio 1:1), and the solid content is 20%. The coating speed is 75 mm / s, the coating width is 6 mm, and the release layer thickness is 0.08 μm. (3) The copper layer edge was fixed by vacuum adsorption, the peeling angle was 150° and the peeling speed was 15m / min.

[0044] Example 4 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, except that in step (5), a hot knife cutting method is used instead of laser cutting, the cutting temperature is 300℃, the cutting pressure is 0.5MPa, and the cutting speed is 50mm / s.

[0045] Example 5 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, the only difference being that in step (5), a hot knife cutting method is used instead of laser cutting, the cutting temperature is 200℃, the cutting pressure is 0.1MPa, and the cutting speed is 10mm / s.

[0046] Example 6 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, except that in step (5), a hot knife cutting method is used instead of laser cutting, the cutting temperature is 400℃, the cutting pressure is 1MPa, and the cutting speed is 100mm / s.

[0047] Example 7 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, the only difference being that: in step (4), adhesive tape is used for peeling, the peeling angle is 170°, and the peeling speed is 20m / min.

[0048] Example 8 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, except that: in step (1), a PET film with a thickness of 2 μm is selected; in step (2), the thickness of the release layer is set to 0.01 μm; in step (3), the thickness of the copper layer is 0.5 μm; in step (4), adhesive tape is used for peeling, the peeling angle is 135°, and the peeling speed is 1 m / min.

[0049] Example 9 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, the only difference being that: in step (5), the laser wavelength of the laser cutting is 243nm, the laser power is 15W, the pulse frequency is 200kHz, and the cutting speed is 200mm / s.

[0050] Example 10 This embodiment provides a method for preparing a composite current collector, the steps of which are the same as those in Embodiment 1, the only difference being that: in step (5), the laser wavelength of the laser cutting is 455nm, the laser power is 50W, the pulse frequency is 1000kHz, and the cutting speed is 300mm / s.

[0051] Comparative Example 1 This comparative example provides a copper foil with a thickness of 4μm as a current collector.

[0052] Comparative Example 2 This comparative example provides a method for preparing a composite current collector, the steps of which are the same as those in Example 1, except that: no release layer is set, and no peeling and cutting steps are included.

[0053] Experimental Example 1 The composite current collectors prepared in Examples 1-10 and Comparative Example 2, as well as the copper foil current collector of Comparative Example 1, were subjected to performance tests, including peel strength tests after tab welding.

[0054] The composite current collectors obtained in Examples 1-10 and Comparative Example 2, as well as the copper foil current collector in Comparative Example 1, were subjected to performance tests, including peel strength tests after tab welding.

[0055] 1. Peel strength test after electrode welding (the test measures the strength of the electrode peeling off from the composite current collector): This test is used to evaluate the ability of the weld interface to resist peeling damage after the exposed area (i.e., the "bare area") of the composite current collector is ultrasonically welded with an external electrode (nickel sheet). It indirectly reflects the cleanliness, density, and metallurgical bonding quality of the exposed area's metal layer surface with the welded electrode.

[0056] Sample preparation: The composite current collectors obtained in Examples 1-10 and Comparative Example 2, as well as the copper foil current collector of Comparative Example 1, were stacked in 15 layers. Then, a standard ultrasonic welding machine (frequency 20kHz, welding pressure 0.3MPa, welding time 0.2s) was used to weld pure nickel tabs with a size of 10mm×40mm and a thickness of 0.1mm to the center of the exposed area of ​​the 15-layer stacked composite current collectors of each example and comparative example. The welding coverage area was 3mm×3mm.

[0057] Test method: The welded specimens were fixed on the fixture of a universal tensile testing machine. In each embodiment and comparative example, the nickel electrode tabs were continuously peeled at a peeling speed of 50 mm / min and a peeling angle of 180°. The average force (N) during the stable phase of the peeling process was recorded. Ten samples were taken from each embodiment and comparative example for testing, and the average value was taken.

[0058] 2. Internal resistance of the electrode after welding Test method: Measurements were performed using a precision internal resistance meter at 25℃±2℃. Two probes were placed firmly against the soldered tab and the underside of the electrode, respectively. Ten samples were taken from each embodiment and comparative example for testing, and the average value was recorded.

[0059] The test data is recorded in Table 1.

[0060] Table 1. Performance Test Results

[0061] As shown in Table 1, Comparative Example 2, a conventional "metal-polymer-metal" sandwich structure composite current collector, could not obtain effective data in the peel strength test after tab welding (indicating immediate detachment upon welding), and the internal resistance of the electrode could not be measured (open circuit or extremely high contact resistance). This indicates that conventional composite current collectors, due to the presence of the intermediate polymer layer, are prone to polymer burn-through, incomplete welding, or substrate melting and fracture when directly welding tabs, failing to form an effective welding interface. Consequently, tab connection cannot be achieved directly through ultrasonic welding and must rely on external transfer welding processes. In contrast, Examples 1-10 demonstrate that the pure metal welding area formed by the "release + peeling + removal" process of this invention can effectively solve the tab welding problem caused by the intermediate insulating layer in composite current collectors. It achieves direct metal-metallurgical bonding between the tab and the tab area of ​​the composite current collector, rather than relying on polymer adhesion, thus providing weld point mechanical strength comparable to traditional foil materials. In addition, the pure metal welding area eliminates the resistance barrier of the polymer insulation layer, resulting in extremely low contact resistance. This ensures a high-speed electron transmission channel between the battery electrodes, providing a guarantee for high-rate charging and discharging, and laying the foundation for the industrial application of composite current collectors.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a composite current collector, characterized in that, Includes the following steps: A release coating is applied to the tab area of ​​a polymer substrate, and a release layer is formed after curing. Metallization deposition is performed on the polymer substrate coated with the release layer to form a metal conductive layer on the surface of the polymer substrate. The metal conductive layer of the tab region is peeled off from the surface of the release layer to expose the release layer and the polymer substrate of the tab region; Remove the exposed release layer and the polymer substrate to form a pure metal welding area in the tab region, thus obtaining a composite current collector; The tab region of the polymer substrate is the area on the polymer substrate that is connected to the tab through the metal layer after the metal conductive layer is deposited.

2. The preparation method according to claim 1, characterized in that, The polymer substrate is selected from polyethylene terephthalate, polypropylene or polyimide, and has a thickness of 2μm-10μm. And / or, the polymer substrate further includes dust removal treatment and corona treatment before coating, wherein the power of the corona treatment is 2kW-5kW and the treatment speed is 20m / min-50m / min; And / or, the release layer comprises a release host, a reactive monomer, and a photoinitiator in a mass ratio of (50-80):(10-30):(0.5-2); And / or, the thickness of the release layer is 0.01 μm-0.1 μm; And / or, the thickness of the metal conductive layer is 0.5μm-2μm.

3. The preparation method according to claim 2, characterized in that, The preparation of the release coating includes: mixing the release substrate, reactive monomer and photoinitiator in a mass ratio of (50-80):(10-30):(0.5-2), adding solvent and mixing evenly to obtain the release coating; Preferably, the solvent is selected from at least one of ethyl acetate and butyl acetate; And / or, the solid content of the release coating is 10%-40%; And / or, the release body comprises hexenyl polydimethylsiloxane; And / or, the reactant monomer is at least one of hexafluorobutyl acrylate and perfluoroalkyl ethyl acrylate; And / or, the photoinitiator is at least one selected from 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, and ethyl 2,4,6-trimethylbenzoylphosphonate.

4. The preparation method according to claim 1, characterized in that, The coating method adopts micro-grooved roller coating, slot coating or spraying, with a coating speed of 60mm / s-80mm / s and a coating width of 1mm-8mm; And / or, the curing method is ultraviolet light curing, with an ultraviolet light intensity of 600 mJ / cm². 2 -1000mJ / cm 2 The curing time is 2-5 seconds. And / or, the peel force of the metal conductive layer and the release layer is ≤10N / m.

5. The preparation method according to claim 1, characterized in that, The preparation of the metal conductive layer includes depositing the metal conductive layer on the surface of a polymer substrate by a deposition process; Preferably, the deposition process includes at least one of magnetron sputtering, vacuum evaporation, and electroplating. Preferably, the metal layer is prepared by vacuum evaporation to form a metal layer with a thickness of 0.5 μm-2 μm on the surface of a polymer base film; Preferably, the preparation of the metal layer includes first forming a metal seed layer with a thickness of 30nm-50nm on the surface of a polymer base film by magnetron sputtering, and then thickening the metal layer to 0.5μm-2μm by electroplating.

6. The preparation method according to claim 1, characterized in that, When peeling the metal conductive layer of the tab area from the surface of the release layer, adhesive tape peeling or vacuum adsorption peeling is used. Preferably, the tape is a high-adhesion polyimide tape or an acrylic tape; Preferably, the peeling angle during peeling is 90°-180°, and the peeling speed is 1m / min-20m / min; And / or, the release layer and polymer substrate of the tab area are removed by laser cutting or hot knife cutting; Preferably, the laser cutting parameters are: a nanosecond laser or a picosecond laser, a laser wavelength of 243nm-455nm, a laser power of 15W-50W, a pulse frequency of 200kHz-1000kHz, and a cutting speed of 200mm / s-300mm / s. Preferably, the parameters for hot knife cutting are: cutting temperature of 200℃-400℃, cutting pressure of 0.1MPa-1.0MPa, and cutting speed of 10mm / s-100mm / s.

7. The preparation method according to claim 1, characterized in that, After removing the release layer and polymer substrate of the tab area, the process also includes cleaning the metal surface of the tab area to remove surface oxides and release layer residues. Preferably, the cleaning is performed by wiping the surface of the welding area with a lint-free cloth soaked in an organic solvent, wherein the organic solvent is anhydrous ethanol or acetone.

8. A composite current collector, characterized in that, The composite current collector is prepared by the preparation method described in any one of claims 1 to 7.

9. An electrode sheet, characterized in that, The electrode sheet includes the composite current collector as described in claim 8.

10. A battery, characterized in that, The battery includes the electrode plates as described in claim 9.